Patients experience more support, information and involvement after first-time hospital accreditation: a before and after study in the Faroe Islands. (26th October 2021) - Bergholt, Maria daniella; Falstie-jensen, Anne mette; Brink valentin, Jan; Hibbert, Peter; Braithwaite, Jeffrey; Johnsen, Søren paaske; Von plessen, Christian
Abstract: Background: The impact of hospital accreditation on the experiences of patients remains a weak point in quality improvement research. This is surprising given the time and cost of accreditation and the fact that patient experiences influence outcomes. We investigated the impact of first-time hospital accreditation on patients' experience of support from health-care professionals, information and involvement in decisions. Objective: We aimed to examine the association between first-time hospital accreditation and patient experiences. Methods: We conducted a longitudinal study in the three Faroese hospitals that, unlike hospitals on the Danish mainland and elsewhere internationally, had no prior exposure to systematic quality improvement. The hospitals were accredited in 2017 according to a modified second version of the Danish Healthcare Quality program. Study participants were 18 years or older and hospitalized for at least 24 h in 2016 before or 2018 after accreditation. We administered the National Danish Survey of Patient Experiences for acute and scheduled hospitalization. Patients rated their experiences of support, information and involvement in decision-making on a 5-point Likert scale. We calculated individual and grouped mean item scores, the percentages of scores ≥4, the mean score difference, the relative risk (RR) for high/very high scores (≥4) using Poisson regression and the risk difference. Patient experience ratings were compared using mixed effects linear regression. Results: In total, 400 patients before and 400 after accreditation completed the survey. After accreditation patients reported increased support from health professionals; adjusted mean score difference (adj. mean diff.) =   1.99 (95% confidence interval (CI): 1.89, 2.10), feeling better informed before and during the hospitalization; adj. mean diff. =   1.14 (95% CI: 1.07; 1.20) and more involved in decision-making; adj. mean diff. =   1.79 (95% CI: 1.76; 1.82). Additionally, the RR for a high/very high score (≥4) was significantly greater on 15 of the 16 questionnaire items. The greatest RR for a high/very high score (≥4) after accreditation, was found for the item 'Have you had a dialogue with the staff about the advantages and disadvantages of the examination/treatment options available?'; RR=   5.73 (95% CI: 4.51, 7.27). Conclusion: Hospitalized patients experienced significantly more support from health professionals, information and involvement in decision-making after accreditation. Future research on accreditation should include the patients' perspective.